Evaluation of customer service quality of platform-based online shopping under blockchain technology. (15th May 2023) - Xiong, Yueming
This work explores the application value of blockchain technology in the evaluation of customer service quality in platform-based online shopping. A three-party sellers, buyers and e-commerce platform evolutionary game model based on blockchain technology is built, and related simulation experiments are performed. The results show that, according to the initial parameters, the evolutionary stable point of the system is (0, 1, 1) after the introduction of the real evaluation mechanism of blockchain e-commerce transaction users. The application of blockchain technology can promote real reviews of buyers and honest management of sellers, curb false reviews and promote the healthy and sustainable development of e-commerce, which has application value.